The Nominalistic principle. A short summary of the contents. E. Hirschberg, Bar, Ilan - Mantilla Pineda, Benigno (Estudios de Derecho, 1972)
The Nominalistic principle. A short summary of the contents. E. Hirschberg, Bar, Ilan